KLAIM TIDAK LAYAK BAYAR PESERTA JAMINAN KESEHATAN NASIONAL DI LAYANAN RAWAT JALAN RUMAH SAKIT JIWA PROF. DR. SOEROJO, MAGELANG - Vera Otifa; Andreasta Meliala; Yulita Hendrartini (Journal of Health Service Management, 2016)
Background: The hospital payment mechanism in National Health Insurance era used INA-CBG's package tarif. The service payment which had given by hospital was paid by Indonesian National Health Insurance Agency with claiming mechanism. There were several factors and causes that affected unfeasible payment claim which could harm the hospital. Objective: Identify the factors that caused the unfeasible payment claim, identify the cause of the unfeasible payment claim, describe the attitude of doctors, the attitude of the leader ship of the hospital, the attitude of the administration RSJS, attitude BPJS Health Magelang and describe RSJS leadership communication to the cause of the unfeasible payment claim in the outpatient service RSJS. Method: This research was an exploratory case study research with single holistic case study design. Analysis unit in this research was outpatient services in Prof. dr. Soerojo Magelang Mental Health Hospital. Research informants were specialized doctor and general practitioner RSJS, Prof. dr. Soerojo Magelang Mental Health Hospital's leaders, Prof. dr. Soerojo Magelang Mental Health Hospital's administrators, and Indonesian National Health Insurance Agency branch in Magelang City. The informant selection used purposive sampling. Data collection used in-depth interview and document observation. Result: The cause of unfeasible payment claim consisted of medical services cause and administrative cause. The cause of medical services most that one episode of outpatient, one episode of inpatient and diagnosis is not emergency. The data difffference between BPJS Kesehatan and medical record, non-emergency diagnosis that considered as emergency diagnosis, one episode of outpatient/inpatient considered as two episodes of outpatient/inpatient. The communication RSJS leaders about unfeasible payment claim is not optimal, the attitude doctor's with less information, the rules have not been clearly linked specifificity RSJS in healthcare delivery, indifffference claim services were they have rendered to the participant JKN, understanding verififier BPJS about medically less in determining the unfeasible payment claim into inconsistencies, too tight in the verifification process and the workload verififier BPJS in RSJS large enough can increase in unfeasible payment claim .The attitude of the leadership of RSJS own conduct follow-up but followup information was not communicated to the doctor RSJS, the attitude of the administration RSJS who respond positively to minimize the unfeasible payment claim. Conclusion: The leaders' communication, doctor's attitude, Indonesian National Health Insurance Agency's attitude and the unpresented operational standard, and procedure in determining steps of unfeasible payment claim were factors that could enhance the incidence of unfeasible payment claim.